2020
DOI: 10.2196/20848
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in Team Communication About Service Statistics Among Health Extension Workers in Ethiopia: Secondary Data Analysis

Abstract: Background In Ethiopia, health extension workers (HEWs) are deployed across the country by the government to meet public health needs. Team communication is important for effective teamwork, but community health workers in low-resource settings like Ethiopia may face challenges in carrying out team meetings to compile service statistics. This is due to the nature of their outreach activities, which requires extensive travel. Objective This study aimed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This study attempted to understand the performance status of selected RMNCH services using routine data in the context of COVID-19 pandemic. However, other studies showed high rates of inaccuracies in health records in Ethiopia [ 40 , 41 ], and as we used routine HMIS data this study may share the inherent limitation of secondary data such as: inconsistency, incompleteness and inaccuracy. Nevertheless, extensive efforts have been made by the research team to ensure the data quality.…”
Section: Discussionmentioning
confidence: 99%
“…This study attempted to understand the performance status of selected RMNCH services using routine data in the context of COVID-19 pandemic. However, other studies showed high rates of inaccuracies in health records in Ethiopia [ 40 , 41 ], and as we used routine HMIS data this study may share the inherent limitation of secondary data such as: inconsistency, incompleteness and inaccuracy. Nevertheless, extensive efforts have been made by the research team to ensure the data quality.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the researcher has used a systematic review table for presenting the findings as well as created specific points for discussing those findings. Thereafter, the researcher has used some specific key terms for finding appropriate journals such as e-payment market, Indian business sector, Covid-19 and economic growth (Lee, 2020). The usage of the secondary sources does not require much time and expenses which is one of the reasons for using these sources.…”
Section: Methodsmentioning
confidence: 99%